Penerapan Kompensasi Dalam Meningkatkan Kinerja Karyawan Menurut Perspektif Ekonomi Islam: Studi pada BPRS HIK Insan Cita Artha Jaya Bogor - Luthfia Luthfia; Sukarna Sukarna (Economic Reviews Journal, 2023)
Compensation is all income in the form of money, direct and indirect goods received by employees as compensation for services provided to the company. Performance is defined as the ability of employees to perform certain skills, this compensation has a reciprocal relationship with employee performance. This study aims to determine how the compensation system run by BPRS HIK Insan Cita Artha Jaya is in accordance with Islamic economics. The research method used is descriptive qualitative, data collection techniques in this study are observation, interviews and documentation. This method describes, analyzes and draws conclusions from the data obtained in the field. The results of the study indicate that the compensation system refers to the principles of fairness, and feasibility. According to the Islamic economic perspective, the provision of compensation to BPRS HIK Insan Cita Artha Jaya is in accordance with Islamic economic principles and is in accordance with Law No. 13 of 2003 article 86 concerning employment which requires that "Employers must provide health and safety support facilities for workers. the work they do. Keywords: Compensation, Performance, Islamic Economics